Last things : a graphic memoir of loss and love - Moss, Marissa (Conari Press, 2017)
After returning home from a year abroad, Marissa's husband, Harvey was diagnosed with ALS. The disease progressed quickly and Marissa was soon consumed with caring for Harvey while trying to keep life as normal as possible for their children. This is not a story about the redemptive power of terminal illness.